VD_FINDINFO HC / 2011 / 220 vom 7. April 2011 - VD Tribunal cantonal (2011)
CONTRAT DE TRAVAIL, JUSTE MOTIF, PROHIBITION DE CONCURRENCE, RÉSILIATION | 340c al. 2 CO, 123 CPC, 124a CPC, 452 al. 2 CPC, 461 al. 1 let. b CPC